PENGARUH STRATEGI THINK-PAIR-SHARE DAN MOTIVASI BELAJAR TERHADAP PEMAHAMAN MEMBACA SISWA DI KELAS X SISWA SMA BINA CIPTA PALEMBANG - Amir Suki (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstrakThis study deals with the influence of Think-Pair-Share (TPS) Strategy and Learning Motivation toward Students’ Reading Comprehension at the Tenth Grade Students of SMA Bina Cipta of Palembang. This study applied experimental method with factorial design with 127 students as population. There were 60 students as the sample of this study. This was taken by using cluster random sampling. The analysis used t-test and two ways ANOVA. Based on the finding of the result of the score of the motivation questionnaire in experimental group shows that 30% students had high motivation and 70% students had low motivation. The result of analysis test of two ways ANOVA showed that there was no a significant interaction effect of TPS strategy and motivation on reading comprehension, since the significant value was 0.270 higher than 0.05.Kata Kunci: Think-Pair-Share (TPS), Motivasi, Pemahaman Membaca